The need for a change in medical research thinking. Eco-systemic research frames are better suited to explore patterned disease behaviors - Sturmberg, Joachim P.; Martin, Jennifer H.; Tramonti, Francesco; Kühlein, Thomas (Frontiers in Medicine, 2024)
Many practicing physicians struggle to properly evaluate clinical research studies – they either simply do not know them, regard the reported findings as ‘truth’ since they were reported in a ‘reputable’ journal and blindly implement these interventions, or they disregard them as having little pragmatic impact or relevance to their daily clinical work. Three aspects for the latter are highlighted: study populations rarely reflect their practice population, the absolute average benefits on specific outcomes in most controlled studies, while statistically significant, are so small that they are pragmatically irrelevant, and overall mortality between the intervention and control groups are unaffected. These observations underscore the need to rethink our research approaches in the clinical context – moving from the predominant reductionist to an eco-systemic research approach will lead to knowledge better suited to clinical decision-making for an individual patient as it takes into account the complex interplay of multi-level variables that impact health outcomes in the real-world setting.